B-111 Sulfotyrosine-mediated V2-V3 interaction stabilizes the HIV-1 envelope trimer facilitating immune evasion. (January 2016) - Guzzo, Christina; Cimbro, Raffaello; Zhang, Peng; Jackson, Robert; Huang, Jinghe; Doria-Rose, Nicole; Schmidt, Stephen; Connors, Mark; Mascola, John; Lusso, Paolo
Abstract : The HIV-1 envelope is a cleverly engineered viral entry machinery featuring a wide array of immune evasion mechanisms. We recently discovered that 2 conserved tyrosines (Y173, Y177) in the second variable (V2) loop of the gp120 envelope glycoprotein can be post- translationally modified by O-sulfation and functionally mimic the sulfotyrosines present in the N-terminal region of CCR5, interacting with the conserved coreceptor-binding site at the base of V3 (Cimbro et al. Proc Natl Acad Sci USA. 2014;111:3152). To get further insights into the functional role of the V2 sulfotyrosines, we examined the effects of tyrosine sulfation modulation and mutagenesis on the neutralization sensitivity of HIV-1. Inhibition of tyrosine sulfation by treatment with sodium chlorate increased HIV-1 sensitivity to soluble CD4 (sCD4) and monoclonal antibodies (mAbs) to CD4-induced (CD4i) or monomer- preferred epitopes; at the same time, neutralization by trimer-specific mAbs was reduced, suggesting that tyrosine sulfation contributes to stabilizing the closed trimer conformation. An even more dramatic effect was observed upon phenylalanine or alanine substitution of the V2 tyrosines, indicating that the tyrosine side-chains play a stabilizing role regardless of their sulfation status. Strikingly, the V2 tyrosine mutants became highly susceptible to neutralization by HIV-1-infected patient sera, including those with low/restricted neutralizing capacity. Altogether, these results document the key role played by the V2 tyrosines, particularly in their sulfated form, as a mechanism of HIV-1 immune evasion.